Expression Pattern of Entire Cytochrome P450 Genes and Response of Defenses in a Metabolic-Herbicide-Resistant Biotype of Polypogon fugax - Yang, Jiajia; Jiang, Minghao; Jia, Siwei; Liao, Min; Cao, Haiqun; Zhao, Ning (Frontiers in Plant Science, 2022)
Enhanced herbicide metabolism mediated by cytochrome P450s has been proposed as one of the major mechanisms of resistance to fenoxaprop-P-ethyl in a metabolic-herbicide-resistant biotype of Asia minor bluegrass (Polypogon fugax Nees ex Steud.). Upon pre-treatment with the P450 inhibitor piperonyl butoxide, a remarkable reduction in metabolic rates of the phytotoxic fenoxaprop-P has been observed in the resistant plants, implying that constitutive and/or fenoxaprop-P-ethyl-induced up-regulation of specific P450 isoforms are involved in the fenoxaprop-P-ethyl resistance. However, which P450 gene(s) were responsible for the metabolic resistance is still unknown. In this present study, based on the abundant gene resources of P. fugax established previously, a total of 48 putative P450 genes were isolated from the metabolic-herbicide-resistant plants and used for gene expression analysis. The most suitable reference genes for accurate normalization of real-time quantitative PCR data were first identified in P. fugax and recognized as actin (ACT), 18S rRNA (18S), and ribulose-1,5-bisphosphate carboxylase oxygenase (RUBP) under fenoxaprop-P-ethyl stress, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and elongation factor 1α (EF1α) under mesosulfuron-methyl stress, and ACT, EF1α, eukaryotic initiation factor 4a (EIF4A), and 25S rRNA (25S) at different growth stages. Expression analysis of the putative P450 genes revealed that six genes, respectively, annotated as CYP709B1, CYP71A1-4, CYP711A1, CYP78A9, P450-11, and P450-39 were up-regulated more than 10-fold in the resistant plants by fenoxaprop-P-ethyl treatment, and all of them exhibited constitutively and/or herbicide-induced higher transcript levels in the fenoxaprop-P-ethyl-resistant than in the susceptible plants. Three genes, respectively, annotated as CYPRO4, CYP313A4, and CYP51H11 constantly up-regulated in the resistant than in the susceptible plants after fenoxaprop-P-ethyl treatment. Up-regulated expressions of these specific P450 genes were consistent with the higher P450 contents determined in the resistant plants. These results will help to elucidate the mechanisms for P450-mediated metabolic-herbicide resistance in P. fugax as well as other grass weed species.